Investigating the potential for utilising a water equity metric to benchmark differential access in Global South cities: a case study of Cape Town - Hoosen, Naadiya (Department of Environmental and Geographical Science, 2025)
In the wake of the day-zero drought the City of Cape Town (CCT or the City) has made the commitment to become water sensitive in its Water Strategy (CCT, 2019). According to the United Nations SDG 6.1, universal access to water has to take priority in any form of water policy. This is reflected in the principles of water sensitive design where equitable and universal access to water is a core tenet. This study assessed the state of equity in the domestic water sector of the City of Cape Town using the Gini Coefficient and the Palma ratio. Both these metrics were selected to determine how access to water and water consumption were distributed averagely throughout the population with the Gini coefficient, as well as between the most resource rich and resource poor with the Palma Index. This was done to complement the Urban Water Metabolism- a water mass balance analysis done for the City by Atkins et al., (2021). By providing a complimentary metric, much like performance indicators used by Paul et al., (2018), Renouf et al., (2017) and Kenway et al., (2011) to analyse the underlying state of equity within the context of the whole-system. The Urban Water Metabolism provides an overview of the City's water budget and the flows of water throughout the city before it finally exits the system. The addition of these equity metrices to benchmark and compare the state of equity can provide valuable information for decision makers to determine if the implementation of water policy, such as those aimed at making Cape Town more water sensitive, have a positive or adverse effect on equity- a point that becomes especially salient during times of low water availability. 141 suburbs in the metropolitan were assessed using the population and total water consumption for a period between April 2017 to April 2018 to determine a figure for the Gini coefficient and Palma ratio which were found to be 0.30 and 4.18 respectively. The Gini coefficient for levels of access to a flush toilet, as well as access to piped water in a dwelling for the suburb households, was also determined and found to be 0.07 and 0.15 respectively. The results of this study revealed that the Gini coefficient and Palma ratio for the City are substantially higher than the Gini Coefficient of the Western Cape (0.06) and the Gini Coefficient and Palma ratio of South Africa nationally (0.27, 0.95) determined in a study by Cole et al., (2018). This difference in the level of inequity represented by the Gini Coefficient at the national and provincial level may highlight the value of working with data at smaller scales and disaggregating data to provide a more nuanced picture of inequity.